Postprandial symptoms in dysmotility-like functional dyspepsia are not related to disturbances of gastric myoelectrical activity - Oba-Kuniyoshi,A.S. (2004)
Gastric dysrhythmias, such as tachy- or bradygastria, have been reported in patients with functional dyspepsia (FD), but their role in symptom production is uncertain. It is also not known whether gastric dysrhythmias in these patients can be elicited by physiological gastric distension with a meal. We investigated the relationships between symptoms after ingestion of different volumes of water following a test meal and gastric dysrhythmias in FD patients. Fourteen patients with dysmotility-like FD and 13 healthy volunteers underwent paired electrogastrography (EGG) studies. Fasted subjects ingested 150 ml of yoghurt with either 150 ml (low volume) or 300 ml (high volume) water in random order. Fasting and fed EGGs with monitoring of symptoms were performed in both studies. Ten FD patients (71.4%) reported upper abdominal discomfort and bloating after the low volume meal, but only one (7.1%) presented an abnormal EGG (dominant frequency in the 2-4-cpm range: 58%). Following the high volume meal, 7 patients (50%) had symptoms, but none had EGG abnormalities. No significant differences were found between FD patients and controls for any of the EGG variables, in any test. In FD patients with postprandial symptoms, the percentage of the EGG dominant frequency in the normal range (median, 84.6%; range, 76.0-100.0%) was similar (P > 0.20) to that in those without symptoms (88.5%; 75.0-100.0%). We conclude that disturbances of gastric myoelectrical activity are unlikely to play a role in the origin of postprandial upper abdominal discomfort and bloating in dysmotility-like FD.